Analisis Faktor Determinan Budidaya Pen Culture Ikan Napoleon (Cheilinus undulatus) Dalam Potensi Pengembangan Kabupaten Natuna - Akmal, Achmad; Anwar, Kasful; Ridhowati, Sherly (Universitas Batangahari Jambi, 2026)
This study investigates the influence of stocking density, seed quality, environmental conditions, and technology on production performance, with management serving as a mediating variable in aquaculture enterprises. A quantitative research design was applied using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Evaluation of the measurement model demonstrated that all constructs satisfied validity and reliability requirements. Outer loading values exceeded 0.70, Average Variance Extracted (AVE) ranged from 0.603 to 0.770, and Composite Reliability values were between 0.881 and 0.944. Discriminant validity was confirmed using both the Fornell–Larcker criterion and the Heterotrait–Monotrait (HTMT) ratio, with all values below 0.90. The structural model analysis showed that the proposed model explained 49.4% of the variance in production performance (R² = 0.494) and 7.3% of the variance in management (R² = 0.073). Hypothesis testing revealed that management had a strong and significant positive effect on production performance (β = 0.681; t = 12.720; p < 0.001), supported by a large effect size (f² = 0.850). Conversely, stocking density, seed quality, and environmental factors did not exhibit significant direct effects on either management or production. Technology showed no direct impact on production; however, it positively influenced management and demonstrated a marginally significant indirect effect on production through management.